Analisis Hasil Pembelajaran Kolaboratif dalam Berkarya Tanah Liat Siswa Kelas IV SDN 3 Buwaran - Hermawan, Andika; Shokib Rondli, Wawan; Fajrie, Nur (Universitas Sultan Ageng Tirtayasa, 2024)
Effective learning must be supported by learning based on cultural approaches around where students live. Through real learning in work, it is hoped that it will be able to provide space for students to be creative. This is the background for researchers to apply collaborative learning in creating fine arts using clay as a medium. This research aims to analyze the results of collaborative learning in creating fine arts using clay as a medium for fourth grade students at SDN 3 Buwaran. Through fine art creation activities using clay as a medium, it is aimed to provide real experience to class IV students at SDN 3 Buwaran, so that students' knowledge and insight regarding clay crafts can increase. Fajrie's theory underlies this research that by working with clay children can express their ideas and creativity. The research method used in this research is the Qualitative Narrative Inquiry method. Data collection in this research was interviews, observation and documentation. The results of the research show that the results of collaborative learning in creating fine art using clay media are that class IV students at SDN 3 Buwaran are able to create different and unique works of fine art from clay according to their respective characteristics.